Montgomery's Federal Taxes–Corporations and Partnerships, 1951-52 / Montgomery's Federal Taxes–Estates, Trusts and Gifts, 1951-52 (Book). - Cannon, Arthur M.; Lasser, J. K. (The Accounting Review, 1952)
Reviews two volumes the book "Montgomery's Federal Taxes." Vol 1., "Corporations and Partnerships, 1951-52," by Robert H. Montgromery, Conrad B. Taylor, Mark E. Richardson; vol. 2, "Estates, Trusts and Gifts, 1951-52," by Robert H. Montgromery, James O. Wynn, C. Harold Blattmachr.